2012
DOI: 10.1128/jcm.01108-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus Type 18 E7 Oncoprotein in Cervical Smears: a Feasibility Study

Abstract: Persistent infections by high-risk human papillomaviruses (HPVs) are the main etiological factor for cervical cancer, and expression of HPV E7 oncoproteins was suggested to be a potential marker for tumor progression. The objective of this study was to generate new reagents for the detection of the HPV18 E7 oncoprotein in cervical smears. Rabbit monoclonal antibodies against recombinant E7 protein of HPV type 18 (HPV18) were generated and characterized using Western blotting, epitope mapping, indirect immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…HPV-18 E7 oncoprotein expression was determined by Western blotting, using monoclonal rabbit anti-HPV-18 E7 antibodies (clone 143-7) (19). These experiments revealed that depletion of p16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV-18 E7 oncoprotein expression was determined by Western blotting, using monoclonal rabbit anti-HPV-18 E7 antibodies (clone 143-7) (19). These experiments revealed that depletion of p16…”
Section: Resultsmentioning
confidence: 99%
“…Equal amounts of protein were subjected to SDS-PAGE (12.5% acrylamide) and blotted onto a polyvinylidene difluoride (PVDF) membrane. Membranes were blocked with 5% skim milk in PBS-0.1% Tween 20 and incubated overnight with the following primary antibodies: rabbit polyclonal antiserum to HPV-16 E7 (5), monoclonal rabbit anti-HPV-18E7/anti-HPV-45E7 antibodies (clone 143-7 [19]), anti-human p16…”
Section: Methodsmentioning
confidence: 99%
“…New technologies for cervical cancer screening are urgently needed. Previous studies suggest that high-risk HPV E7 proteins are regularly expressed in cervical carcinoma and in their high-grade precursor lesions, suggesting that high-risk E7 oncoproteins are necessary for this cancer and may serve as new tumor biomarkers [10,[17][18][19][20]. In the present study, we developed and validated a new ELISA test capable for the simultaneous detection of the E7 proteins of HPV-16, HPV-18, and HPV-45.…”
Section: Introductionmentioning
confidence: 90%
“…The generation of rabbit monoclonal antibodies (RabMAbs) 42-3 and 143-7, as well as polyclonal goat antisera to HPV-16 E7 (Goat 1) and HPV-18 E7 (Goat 2), was described previously [17,20]. Increasing amounts of the E7 proteins encoded by HPV-16, HPV-18, HPV-45 and HPV-11 (low risk) were added in 100 µl coating buffer (0.1 M NaHCO 3 , pH 9.6) to each well of a 96-well plate (Maxisorp F, Nunc, Vienna, Austria) and incubated overnight at 4°C.…”
Section: Characterization Of Rabmabs and Polyclonal Goat Antibodies Bmentioning
confidence: 99%
See 1 more Smart Citation